The effect of giving papaya fruit on the sufficiency of breast milk in post-post mothers - Fenny Fernando; Melia Pebrina; Dewi Fransisca; Ramah Hayu (Institute of Computer Science (IOCS), 2026)
Exclusive breastfeeding coverage in the Lubuk Buaya Community Health Center, Padang, remains low at 53.2%. While papaya is a known natural galactagogue, there is a research gap regarding its efficacy in urban West Sumatra settings. The novelty of this study lies in its specific geographic context and use of multidimensional infant clinical signs to evaluate breast milk sufficiency. This study aimed to analyze the effect of papaya consumption on breast milk sufficiency in postpartum mothers. Using a pre-experimental one-group pretest–posttest design, 16 postpartum mothers (aged 20–35 years, nursing infants 0–6 months) were selected via purposive sampling. They consumed 200g of ripe papaya three times daily for seven days. Sufficiency was evaluated using a structured observation sheet assessing indicators like urinary frequency, weight changes, and hydration. Analyzed via the Wilcoxon Signed Rank test, inadequate sufficiency dropped from 56.2% to 0%. The average score increased from 3.44 to 4.69, reflecting a mean increase of 1.25 points (p=0.001, large effect size r=0.62). Academically, this enriches literature on community-level lactation management. Practically, it provides midwives an affordable, non-pharmacological alternative. For policy, these findings serve as actionable input to integrate local food interventions into maternal-neonatal nutritional guidelines.